1998
DOI: 10.1016/s0022-5347(01)62517-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Cystectomy, Microvessel Density and Prognosis in Stage T1 Transitional Cell Carcinoma of the Bladder

Abstract: Patients with T1 bladder cancer have a high risk of recurrence and progression. Tumor progression has a significant negative impact on survival. Neither grade nor early tumor recurrence predicted disease progression. Because early cystectomy did not improve patient outcome, we suggest reserving cystectomy for patients with progression or disease refractory to local therapy. Microvessel density is not a prognostic marker for T1 bladder cancer and has no value in selecting patients with T1 disease for cystectomy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
5

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 34 publications
1
15
1
5
Order By: Relevance
“…Dinney et al evaluated the role of MVD for determining early cystectomy in patients with T1 bladder cancer. They found that MVD did not correlate with recurrence or progression and concluded that MVD had no value in selecting patients with T1 disease for cystectomy [23]. In our study high MVD was correlated with the risk of clinical progression in superficial bladder cancer.…”
Section: Discussioncontrasting
confidence: 58%
“…Dinney et al evaluated the role of MVD for determining early cystectomy in patients with T1 bladder cancer. They found that MVD did not correlate with recurrence or progression and concluded that MVD had no value in selecting patients with T1 disease for cystectomy [23]. In our study high MVD was correlated with the risk of clinical progression in superficial bladder cancer.…”
Section: Discussioncontrasting
confidence: 58%
“…Bladder tumors produce high levels of several stimulatory factors, including VEGF [9,10], bFGF [11,12], and IL-8 [13]. Microvessel density, a surrogate marker for angiogenesis [14], has been shown to be predictive of progression and poor prognosis in invasive TCC [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…TCC of the bladder has a wide spectrum; epidemiological studies clearly delineate several patterns of occurrence and progression [1–3]. Since the pioneering work of Jewett, this spectrum has been divided into two entities, i.e.…”
Section: Introductionmentioning
confidence: 99%